Self-Confidence Through Canva Aplication, Wordwall and Ular Tangga in Solving Algebra Problems - Maryati, Iyam; Yulianti, Yanti (Universitas Suryakancana, 2024)
Self-confidence is a positive attitude that is the most important basic capital in a person to be able to develop his abilities to achieve whatever he wants and can do, both towards himself and the environment or situations he faces, including in learning. However, the Trends in International Mathematics and Science Study (TIMSS) data indicates that Indonesian students' self-confidence still needs to improve by at least 30%. This study assesses junior high school students' confidence in solving algebraic problems. This study employs a qualitative, descriptive research methodology. To analyse the data, conclusions were drawn, and the percentage of students who used the Canva app, Wordwall, and the Ular tangga game to gain confidence in their ability to solve algebraic problems was described. Thirty-six junior high school students in class VII served as the research subjects. Cognitive test sheets and observations were the study tools used. This study looked at four characteristics of self-confidence: 1) Act independently in making decisions; 2) Have a positive self-concept; and 3) Dare to voice thoughts. When choosing the learning models and media to employ in teaching and learning activities, teachers can benefit from the findings of this research. Thus, the Canva application and Wordwall media are able to increase self-confidence in class VII junior high school students.